Respuesta :

Answer:

-5/12

Step-by-step explanation:

2 1/6 -(-1 3/4) =

-13/6 - (-7/4) =

-5/12

-5/12

Step-by-step explanation:

Step 1: Eliminating a negative and changing our operation

−2 1/6 + 1 3/4

Step 2: Rewriting our equation with parts separated

-2 1/6 + 1 + 3/4

Step 3: Solving the whole number parts

−2 + 1 = −1

Step 4: Solving the fraction parts

−1/6 + 3/4 = ?

Step 5: Find the LCD of 1/6 and 3/4 and rewrite to solve with the equivalent fractions.

LCD = 12

−2/12 + 9/12 = 7/12

Step 6: Combining the whole and fraction parts

−1 + 7/12 = −5/12